The Correlation Between Self-Efficacy and Medication Adherence with the Quality of Life of Pulmonary Tuberculosis Patients at Randuagung Health Center, Lumajang Regency - Nur Aifa; Suhari Suhari; Ro'isah (KHD Production, 2024)
Tuberculosis (TB) remains a significant health issue in Indonesia. Individuals diagnosed with pulmonary tuberculosis often have a negative response to their illness, which impacts their quality of life. Factors that can enhance the quality of life of clients include self-efficacy and medication adherence. The purpose of this study was to analyze the Correlation between self-efficacy and medication adherence with the quality of life of pulmonary tuberculosis patients at Randuagung Health Center, Lumajang Regency. This study employed a cross-sectoinal methodology and a correlational design. Twenty respondens made up the study’s sample. Self-efficacy questionnaires, MMAS-8, and WHOQOL-BREF were used in the study. The data analysis employed Spearman's Rho. This study has been submitted and approved by the ethics committee at Universitas Hafshawaty Zainul Hasan. The results indicated that the majority of patients had high self-efficacy, with 13 respondents (65%), the majority adhered to medication, with 15 respondents (75%), and the majority had a good quality of life, with 14 respondents (70%). The study showed a correlation between self-efficacy and the quality of life of pulmonary tuberculosis patients with a p-value of 0.000 (p<α=0.05) and a correlation strength (r) of 0.898, indicating a very strong positive correlation. There was also a correlation between medication adherence and the quality of life of pulmonary tuberculosis patients with a p-value of 0.000 (p<α=0.05) and a correlation strength (r) of 0.882, indicating a strong positive correlation. A good quality of life is crucial for individuals with pulmonary tuberculosis because it allows them to manage their illness and maintain health effectively, leading to well-being and the ability to engage in physical activities in their lives. High self-efficacy and medication adherence play a significant role in the quality of life of patients. High or moderate self-efficacy and adherence to medication contribute to a good quality of life, and vice versa.